NATURE IN FEDERICO GARCÍA LORCA’S POETRY - Zaynul Abedin (Department of English Literature, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
One of the integral figures of ecocriticism, nature has been at the origin of incredibly flourishing critical interventions into literary works with a commitment to environmental justice. Such critical readings have as their goal to highlight the meticulous work that goes into the literary world's carefully hidden stylistic components. Additionally, it directs the poet toward an obligation to uphold the inviolable sacredness of nature, which is the foundation of poetry. This paper aims at understanding the concept of nature by reading a select group of Lorca’s poems to show that Lorca’s constant attachment to nature. This paper uses comparative study as the approach to the analysis since the paper observes Lorca’s selected poems. The findings show that Lorca’s poems provide insights about his love to Andalusia and also his love to nature. Thus, as a poet, Lorca can be understood as the ecocritically conscious poet of his time.